Standardization of the eucalyptus grandis sawmill process of searching forcompetitiveness necessary for an export opening - Vallejo, Marcelo Rodolfo (2021)
Fil: Vallejo, Marcelo Rodolfo. Universidad del Salvador. Facultad de Agronomía; Argentina.